The Effect of Audit Fee and Machiavellianism on Auditor Independence with Professional Ethics as a Moderating Variable - Mujiono, Mujiono; Jonnardi, Jonnardi (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2022)
Abstract The purpose of this study is to examine the factors that influence auditor independence. The research variables consist of audit fees, Machiavellian traits, and professional ethics as moderating variables. The research sample is an auditor who works at KAP in Bandung as many as 44 people. The results of the study prove that 1) Audit fees have a negative effect on auditor independence, 2) Machiavellian nature has a negative effect on auditor independence, 3) Professional ethics is proven to be a moderating variable that affects the relationship between audit fees and auditor independence, and 4) Professional ethics is proven as a moderating variable. moderating variables that affect the relationship between Machiavellian nature and auditor independence.